Preliminary evidence of immune infiltration and neutrophil degranulation in peripheral blood of non-obese OSA patients related to cognitive decline - Qingqing Liu; Yanru Ou; Ting Liu; Yuming He; Xiangming Quan; Ruoyun Ouyang; Zhihui Shi (Scientific Reports)
Abstract Obstructive sleep apnea (OSA) patients have varying degrees of cognitive impairment, but the specific pathogenic mechanism is still unclear. Meanwhile, poor compliance with continuous positive airway pressure (CPAP) in OSA prompts better solutions. This study aimed to identify differentially expressed genes between the non-obese OSA patients and healthy controls, and to explore potential biomarkers associated with cognitive impairment. Cohorts of healthy control (n = 20) and non-obese, treatment-naïve OSA patients (n = 20) were recruited. We collected their peripheral blood mononuclear cells and neutrophils, and their cognitive performances were evaluated by the Montreal Cognitive Assessment (MoCA). The differentially expressed genes were identified by bioinformatic analysis and confirmed by PCR. Imbalanced immune cell proportions were assessed by Cibersort. Biomarkers related to enriched cellular pathways were measured by ELISA. OSA patients showed a significant decline in overall cognitive function and were associated with higher daytime sleepiness scores. Multiple signaling pathways were enriched in the non-obese OSA cohort, including upregulation of neutrophil-degranulation. Increased monocyte proportion and decreased NK cell proportion were figured out. The relevant genes, including upregulated defensin alpha 4 (DEFA4), haptoglobin (HP), survivin (BIRC5), and suppressed interferon gamma (IFNG) expression were detected. The relative expression of DEFA4 was significantly correlated with the MoCA score and sleep parameters. Biomarkers such as myeloperoxidase (MPO), H2O2, and lipocalin-2, as representatives of neutrophils’ activation, elevated significantly in the OSA group. The data demonstrated a positive correlation between MPO and oxygen desaturation index (ODI) and a negative correlation between MPO and lowest oxygen saturation (LSaO2). The level of Lipocalin-2 was positively correlated with apnea-hypopnea index (AHI) and ODI and negatively correlated with LSaO2 and MoCA score. We also observed a negative correlation between H2O2 and mean oxygen saturation (MSaO2). Degranulation of neutrophils was activated in non-obese OSA patients without other complications. The process is related to OSA severity and cognitive impairment, implying its role in pathogenesis.